Application of a Hydrological MIKE HYDRO River – UHM Model for Valea Rea River (Romania). Case Study, Flash Flood Event Occurred on August 1st, 2019 - István KOCSIS (Aerul şi Apa: Componente ale Mediului, 2020)
On August 1, 2019, the atmospheric instability was very pronounced in the hydrographic basin related to the Călinești-Oaș Reservoir, the main phenomenon being the local rainstorms, of very high intensity. The successive radar images, observed in real time, predicted the outbreak of a hydrometeorological event with a strong impact in the catchment basin of the Huta Certeze hydrometric station, on Valea Rea river (the upper hydrographic basin of the Tur river, Oașului Mountains, Satu-Mare district). In a very short time of only 4 hours, a total of 132.5 mm precipitation was measured, which generated a flash flood with a single peak, exceeding the flooding stages, with a maximum discharge of 46.6 m3/s. Being an extreme hydrometeorological phenomenon, the question arises to verify whether it is possible to modeling a flash flood of an almost unprecedented magnitude. For modelling purpose MIKE HYDRO River – UHM (Unit Hydrograph) has been selected, being the most suitable for the unit hydrograph method, when the inputs are generated by a single storm event. A GIS based application; ArcMap was used to delimit the affected catchment area. The simulated discharge hydrographs were compared with the observed one at the Huta Certeze hydrometric station, which represent the closing point of the studied basin. The obtained results confirm the modeling’s veracity. Therefor MIKE HYDRO River can be used for forecasting water flows to rivers or lakes, for estimating water resources, as well as for river basin management.